2006
DOI: 10.1227/01.neu.0000228683.79123.f9
|View full text |Cite
|
Sign up to set email alerts
|

Visual Outcome of Tuberculum Sellae Meningiomas after Extradural Optic Nerve Decompression

Abstract: Adding early optic nerve decompression by extradural clinoidectomy and optic canal unroofing to a frontopterional approach seemed to improve visual outcomes because there were no instances of visual deterioration. Simpson Grade 1 to 2 removal was possible in all patients with primary surgery, whereas recurrent cases could only be treated with lower grades of radicality. Radical removal, however, required readiness to reoperate for cerebrospinal fluid leakage at the site of the drilled tumor origin in bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
118
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(125 citation statements)
references
References 17 publications
1
118
0
6
Order By: Relevance
“…Endonasal approaches have been recently used for treating fronto-basal meningiomas 9-11 but, despite of its advantages, most authors prefers intracranial approaches for resecting olfactory meningiomas 3,4,6,[12][13][14][15] . We have used bifrontal craniotomy with or without unilateral orbital rim resection for resection of these tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endonasal approaches have been recently used for treating fronto-basal meningiomas 9-11 but, despite of its advantages, most authors prefers intracranial approaches for resecting olfactory meningiomas 3,4,6,[12][13][14][15] . We have used bifrontal craniotomy with or without unilateral orbital rim resection for resection of these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Infection and cerebrospinal fluid leak are potential risks for entering the frontal sinus or the etmoidal cells. Exenterates the sinus mucosa, resection of the posterior wall of the frontal sinus and packing the sinus with muscle are important precautions to avoid these complications 4,13 . In our series, local postoperative complications were observed in 23.5% of patients with olfactory groove meningiomas (soft tissue infection, epidural empiema/osteomyelitis, and osteomyelitis).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with the removal of the orbital bar and orbital roof, the decompression of the optic nerve via clinoidectomy, the unroofing of the optic canal, and the opening of the falciform ligament have contributed to the significant postoperative improvement of the visual function of these patients 11,17,18,21,[23][24][25] . Ohta et al 10 reported on 21 cases of complete resection of TSMs in a series of 33 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mathiesen and Kihlström 23 reported on a series of 29 patients with TSMs, which included 23 primary cases and six recurrences. These authors reported on extradural clinoidectomy and unroofing of the optic nerve and of the optic canal followed by intradural release of the optic nerve.…”
Section: Discussionmentioning
confidence: 99%